COMPARATIVE FINANCIAL PERFORMANCE EVALUATION OF THE SELECTED LEASE FINANCING COMPANIES IN INDIA - P. Senthil Kumar; Dr. B.Rajendran (IJRDO - Journal of Business Management, 2025)
Lease financing is a typical form of financial assistance provided to the borrowers. In this case, the loan is not provided to the borrowers. However, if they purchase fixed assets, the cost of such assets is paid by the lease financing companies to the vendors directly. The borrowers have to repay the cost of assets in instalments along with interest payable. There are many lease financing companies functioning in India. It is to be noted that since these companies are involved in providing financial assistance, their financial performance is to be evaluated frequently in order to understand the financial position of these companies. This study has been undertaken to evaluate the comparative financial performance of the selected lease financing companies in India. This study has delved into the comparative financial performance of Cholamandalam Finance Limited, Poonawalla Fincorp Limited and Bajaj Finance Limited. These companies have been selected under simple random sampling method among the lease financing companies in India. The study covers a period of 10 financial years starting from 2014-15 to 2023-24. The secondary data collected from the annual reports of the selected companies have been analyzed using mean, standard deviation, coefficient of variation, compounded annual growth rate and coefficient of correlation. The results revealed that the performance of Cholamandalam Finance was better with reference to profitability while the liquidity performance of Poonawalla Fincorp Limited was better than the other companies.